Antioxidant and anti-angiogenic effects of mushroom phenolics-rich fractions. (August 2015) - Lin, Shaoling; Ching, Lai Tsz; Chen, Jialun; Cheung, Peter C.K.
Highlights: Phenolic profile of the ethyl acetate fraction of Pleurotus tuber-regium. Antioxidant activity of phenolics-rich ethyl acetate fraction from Pleurotus tuber-regium. In vitro and in vivo anti-angiogenic effects of the mushroom phenolics-rich fraction. Association between the antioxidant and anti-angiogenic effects of mushroom extract. Abstract: An ethyl acetate fraction (EAF) from the mushroom sclerotium of Pleurotus tuber-regium ( PTR ) was rich in total phenolics (41.4 ± 0.67 mg/g extract) constituting 58% chlorogenic acid and 21% syringic acid. EAF had stronger antioxidant activity than other fractions in terms of 2, 2-diphenyl-1-picrylhydrazyl (DPPH), 2, 2′-azino-bis (3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) and hydrogen peroxide scavenging activity. EAF significantly inhibited blood vessel development in the wild type and transgenic zebrafish embryos demonstrated by endogenous alkaline phosphatase assay and microscopic imaging, respectively. In vitro experiments by using human umbilical vein endothelial cells (HUVECs) revealed that EAF was non-cytotoxic but could significantly inhibit vascular endothelial growth factor (VEGF)-induced proliferation, migration and tube formation. Significant inhibition of intracellular superoxide production and VEGFR phosphorylation were found in EAF-treated HUVECs by the 2′7′-Dichlorofluorescein diacetate (DCFH-DA) assay and western blotting, respectively. These results provided the plausible explanations for the link between the antioxidant and anti-angiogenic effects in the EAF which might imply its potential use as a source of mushroom antioxidants with anti-angiogenic properties.